Reversal of experimental paralysis in a human by intranasal neostigmine aerosol suggests a novel approach to the early treatment of neurotoxic envenomation. Issue 1 (24th July 2013) - Lewin, Matthew R.; Bickler, Philip; Heier, Tom; Feiner, John; Montauk, Lance; Mensh, Brett
Key Clinical Message Neurotoxic snake envenomation can result in respiratory failure and death. Early treatment is considered important to survival. Inexpensive, heat‐stable, needle‐free, antiparalytics could facilitate early treatment of snakebite and save lives, but none have been developed. An experiment using aerosolized neostigmine to reverse paralysis suggests how early interventions could be developed.